EFEKTIVITAS PIJAT EFFLEURAGE DIBANDINGKAN DENGAN DANCE LABOR DALAM MENGURANGI NYERI SELAMA BERSALIN EVIDENCE-BASED CASE REPORT (EBCR) (Politeknik Kesehatan Kemenkes Bandung, 2022)
BACKGROUND : LABOR PAIN IS ONE OF THE MOST SEVERE FORMS OF PAIN EXPERIENCED BY WOMEN DURING THEIR LIVES. IT IS SEEN AS A COMPLEX PHYSIOLOGICAL PHENOMENON THAT INCLUDES PSYCHOLOGICAL, EMOTIONAL, SPIRITUAL AND PHYSICAL DIMENSIONS.15 THEREFORE, PAIN RELIEF DURING LABOR IS AN IMPORTANT ASPECT OF OBSTETRIC CARE. LABOR PAIN RELIEF METHODS ARE CATEGORIZED INTO PHARMACOLOGICAL METHODS (INHALATION ANESTHESIA, REGIONAL ANESTHESIA, OPIOIDS SUCH AS PETHIDINE) AND NON-PHARMACOLOGICAL METHODS (HYPNOSIS, WATER DELIVERY, ACUPUNCTURE, MASSAGE). METHODS: SEARCHED ON PUBMED, GOOGLE SCHOLAR AND COCHRANE. RESULTS: THE RESULTS OF THE EXPERIMENTAL GROUP WERE FOUND TO BE STATISTICALLY SIGNIFICANTLY LOWER THAN THAT OF THE CONTROL GROUP (P <. 05). MASSAGE CAN REDUCE PAIN DURING CHILDBIRTH. CONCLUSION: MASSAGE CAN REDUCE PAIN DURING CHILDBIRTH